Expressão do fator de transcrição da família ETS : PDEF no câncer colo-retal através de imunohistoquímica - Althoff, Juliana Lorenzoni (2009)
Background: The colon-rectal cancer is the third most frequent neoplasia in the western world with the highest mortality rates. The progression of normal colon tissue to invasiveness neoplasia is follow by several processes called carcinogenesis. Afterwards it converges to the cellular migration and metastasis of the tissue. The metabolic ways of the E26 (Ets) transcription factors, identified in a great variety of species, contributes in this process, by activating or repressing the DNA transcription. Specially, the prostate-derived Ets factor (PDEF) which prognosis and cancer colon-rectal relation action is not completely elucidating at the moment. Methods: A retrospective cohort of patients with pathologic stage I – III colon-rectal cancer, diagnosed and treated in the same institution between 2002 and 2008, was study. Histological and clinical features as well as clinical outcomes and survival were reviewed. The tissue microarrays (TMA), immunohistochemical analysis and image capture quantification were carried out in representative blocks of tumor with antibodies for the detection of the PDEF expression and Ki-67. The endpoints were to determine the prevalence of the PDEF protein expression and its correlation with these population’s prognostic factors. Results: The sample was constituted 46 patients and the median follow-up was 23,2 months. There was a trend towards loss of PDEF protein expression according to the patients’ clinical stage. PDEF expression values were 30,3%, 25,8% and 14,7% in stages I, II and III, respectively. There was not a significant correlation with the lost of PDEF protein expression and the clinical and pathological characteristics along with the proportion of Ki-67 proliferative marker and the patient’s global survival. Conclusions: These results suggest that the PDEF protein, member of the Ets family, act as a repression gene of cancer colon-rectal carcinogenesis. The PDEF expression analysis can be an interesting prognostic marker and a therapeutic target. New studies with more patients and a long follow-up are necessary to validate these results.